Analisis Bahaya Longsor Berdasarkan Sistem Informasi Geografis di Kabupaten Sumedang - Rakhmad Fadillah; Boedi Tjahjono; Fifi Gus Dwiyanti (Postgraduate, University of Mataram, 2024)
Sumedang Regency has a hilly landscape, making it one of the 13 cities/regencies in West Java Province that are prone to landslides. A total of 80 landslide incidents were recorded from 2019 to 2023. These landslides resulted in 45 fatalities, 53 injuries, and damage to 317 infrastructure units. This situation indicates the importance of conducting an analysis of landslide hazard distribution. The landslide hazard distribution analysis is carried out using a weighting and scoring method on the parameters used, which include: slope gradient, rainfall, actual land cover, landform, lithology, and soil type. Based on these parameters, four landslide hazard classes were identified in Sumedang Regency: low, medium, high, and very high hazard classes. Proportions of these hazard are as follows: high hazard class (42.24%), medium hazard class (40.38%), low hazard class (13.90%), and very high hazard class (3.49%). The low hazard class is mainly found in the northern part of Sumedang Regency, the medium hazard class is widespread in sloping areas, and the high to very high hazard classes are primarily found in the Tampomas mountains and areas with hilly landforms. Slope gradient and rainfall are the factors that most influence landslide hazards, making it necessary to design appropriate mitigation.